Antimicrobial activity of topically-applied soyaethyl morpholinium ethosulfate micelles against Staphylococcus species. (March 2016) - Yang, Shih-Chun; Aljuffali, Ibrahim A; Sung, Calvin T; Lin, Chwan-Fwu; Fang, Jia-You
Aim: Here we evaluated the antibacterial efficacy of soyaethyl morpholinium ethosulfate (SME) micelles as an inherent bactericide against Staphylococcus aureus and methicillin-resistant S. aureus (MRSA).Methodology: The antimicrobial activity was examined by in vitro culture model and murine model of skin infection. Cationic micelles formed by benzalkonium chloride or cetylpyridinium chloride were used for comparison.Results: The minimum inhibitory concentration and minimum bactericidal concentration against S. aureus and MRSA were 1.71–3.42 and 1.71–6.84 μg/ml, respectively. Topical administration of SME micelles significantly decreased the cutaneous infection and MRSA load in mice. The killing of bacteria was caused by direct cell wall/membrane rupture. SME micelles also penetrated into the bacteria to elicit a Fenton reaction and oxidative stress.Conclusion : SME micelles have potential as antimicrobial agents due to their lethal effect against S. aureus and MRSA with a low toxicity to mammalian cells.